2012
DOI: 10.18517/ijaseit.2.4.208
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antibacterial Activity of Thiophenes

Abstract: 2-[Bis(methylthio)methylene]propanedinitrile 1a reacted in one-pot successively with piperidine, sodium sulfide, chloroacetonitrile, and potassium carbonate to afford 3-amino-5-(1-piperidinyl)-2,4-thiophenedicarbonitrile 2a. Similar reaction using the last three reagents with ethyl 2-cyano-3,3-bis(methylthio)acrylate 1b produced ethyl 4-amino-5-cyano-2-(methylthio)thiophene-3-carboxylate 2b. The synthesized compounds were characterized by using FT-IR, 1 H-NMR, 13 C-NMR, and mass spectral data. Antibacterial ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
(10 reference statements)
0
7
0
Order By: Relevance
“…They are significant heterocyclic molecules that are extensively used as precursors in numerous agrochemicals. In addition, several antimicrobial agents carry thiophene ring. Accordingly, and owing to the wide range of biological applications of thiophenes, and in continuation to our work on the synthesis of new compounds of pharmacological interest, we present, herein, the synthesis and characterization of a new series of thiophene‐based compounds, along with their antimicrobial activities.…”
Section: Introductionmentioning
confidence: 99%
“…They are significant heterocyclic molecules that are extensively used as precursors in numerous agrochemicals. In addition, several antimicrobial agents carry thiophene ring. Accordingly, and owing to the wide range of biological applications of thiophenes, and in continuation to our work on the synthesis of new compounds of pharmacological interest, we present, herein, the synthesis and characterization of a new series of thiophene‐based compounds, along with their antimicrobial activities.…”
Section: Introductionmentioning
confidence: 99%
“…Adiwish et al [23] synthesized tetra substituted thiophenes from ketene dithioacetals as represented in Scheme 10. The synthesized compounds 49a and 49b were evaluated in vitro for their antibacterial activity against Gram-positive bacteria ( S. aureus and B. subtilis ) and Gram-negative bacteria ( E. coli and K. pneumonia ) by using agar disc-diffusion technique.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Thiophenes form a major class of bioactive heterocycles. They show a broad spectrum of biological response such as antibacterial, [12][13][14] anti-leishmanial, [1] antifungal, [1,[12][13][14][15] antimicrobial, [12][13][14][15] antitumor, [16,17] anticancer, [16,17] antiinflammatory, [13,14] antiproliferative, [18] molluscicidal [19] and anticonvulsant activity. [20] A literature survey showed that amongst the substituted thiophenes, poly substituted 3-amino thiophenes in particular need to be studied.…”
Section: Introductionmentioning
confidence: 99%